PENGARUH PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) - Nurlaila Hasmi (Journal of Innovation Research and Knowledge, 2022)
This study aims to determine the effect of tax knowledge on land and building taxpayer compliance at the Sungguminasa Village Office, Gowa Regency. This study uses a quantitative approach. Collecting data using a questionnaire, with a sample of 40 taxpayer respondents in the payment of PBB. Data were analyzed using simple linear regression. The results of the study indicate that tax knowledge has a significant effect on compliance with regional development taxpayers at the Sungguminasa Village Office, Gowa Regency.